Integrated nutrient management improves yield, quality and nutrient uptake of baby corn under sub-tropical condition - Mohammed Hossain , Sarker; Sinthia Afsana , Kheya; Farhana , Zaman; Shams Shaila, Islam; Md. Abdul, Kader; AFM Shamim, Ahsan; Ahmed Khairul , Hasan (Plant Science Today, 2025)
A consistent supply of nutrients is critical for reaching optimum quality and output in baby corn. To address this issue, we looked at how integrated nitrogen management affected baby corn growth, productivity, quality, and nutrient absorption. Seven different fertilizer combinations of organic and inorganic fertilizers were administered on three varieties viz., Baby Star, Dream Sweet-3, and MSC No. 001. The study was replicated three times using a split-plot design. Integration of Baby Star variety and 75% recommended dose of chemical fertilizer (RD) + cow dung (CD) @ 10 t ha-1 outperformed all the combinations in terms of plant height, leaf area index, total dry matter, and crop growth rate. This combination took a minimum of days to tasseling and silking. Compared to the solo application of inorganic fertilizer, Baby Star showed a 34% increase in cob yield with husk and a 32% rise in cob yield without husk at 75% RD + CD @ 10 t ha-1. The greatest levels of protein and starch were detected in Baby Star with 75% RD + cow dung at 10 t ha-1, however, the highest levels of total soluble solid (TSS) were found in Dream Sweet-3 with 75% RD + CD @ 10 t ha-1. Baby Star variety also had more N, P, K, and S content at 75% RD + CD @ 10 t ha-1 fertilizer level. Finally, it can be inferred that the Baby Star with 50% RD + CD @ 10 t ha-1 performed better and seemed to be the potential method for sustainable baby corn production.